Differentiated Learning in Islamic Religious Education: A Literature Review of Concepts, Principles, and Implementation - Hana Ayu Safitri; Mahasri Shobahiya; Mohamad Ali; Nurul Asma Khoiriyah (Universitas Muhammadiyah Surakarta, 2025)
PAI learning in schools still tends to be uniform and teacher-centered, so it is not fully able to accommodate individual differences of students. In the context of the Independent Curriculum, differentiated learning is a relevant approach because it is in line with the spirit of